Onomatopoeia in Balinese Fauna Themed Fairy Tales 5th Grade Students of SD N 2 Melaya, Bali (e-Journal of Linguistics, 2026)
While oral traditions heavily influence children's cognitive development, transitioning these auditory memories into structured written forms often presents phonological challenges. This study aims to investigate the phonotactic and structural characteristics of fauna-themed onomatopoeia spontaneously produced by 5th-grade students at SD N 2 Melaya, Jembrana, Bali, within creative fairy tale writing tasks. Employing a qualitative descriptive research design, data were elicited through controlled chained images depicting Balinese endemic fauna and complemented by unstructured interviews. The results reveal that the student-generated texts exhibit four distinct categories of sound imitation: object sounds, animal sounds, human sounds, and expressions of human feelings. Structurally, these onomatopoeic forms are systematically mapped into monosyllabic, bisyllabic, and multisyllabic syllable patterns. These findings demonstrate how children navigate language constraints to map environmental acoustics into orthographic strings (auditory to orthographic mapping). This study offers crucial theoretical insights into child cognitive linguistics and contributes to the written documentation of environmental-based local wisdom